1997
DOI: 10.1159/000185520
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-lnduced Changes in Insulin-Like Growth Factors and Their Binding Proteins in Pregnant Rats

Abstract: Pregnancy is associated with important changes in the insulin-like growth factor (IGF)-insulin-like growth factor binding protein (IGFBP) axis, but the importance of these growth factors for fetal growth is not well understood. We have recently established a maternal hypoxia model that results in significant intrauterine growth retardation in the fetus, and characterized the IGF-IGFBP axis in growth-retarded fetuses. To determine if maternal IGFs and their binding proteins are similarly regulated by hypoxia, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Insulin‐like growth factor binding protein‐3, one of the most abundant proteins in serum, has been known to regulate the IGF axis, which is essential for survival and metabolism of cancer cells in a hypoxic and energy‐limited environment . Insulin‐like growth factor binding protein‐3 has also been shown to inhibit vascular endothelial cell survival and induce normalization of tumor vasculature .…”
Section: Discussionmentioning
confidence: 99%
“…Insulin‐like growth factor binding protein‐3, one of the most abundant proteins in serum, has been known to regulate the IGF axis, which is essential for survival and metabolism of cancer cells in a hypoxic and energy‐limited environment . Insulin‐like growth factor binding protein‐3 has also been shown to inhibit vascular endothelial cell survival and induce normalization of tumor vasculature .…”
Section: Discussionmentioning
confidence: 99%
“…The fetal liver is the primary source of fetal IGFBP-1 during pregnancy (Watson et al 2006;Tapanainen et al 1997). HepG2 cells have been commonly used as a model for human fetal hepatocytes (Wilkening et al 2003;Kelly and Darlington.…”
Section: Models Of Fgrmentioning
confidence: 99%
“…Previous studies have also shown effects of IH L on energy metabolism via regulation of genes encoding for glucose transporters and glycolytic enzymes (29,61,63), primarily through modulation of hypoxia-inducible factor 1-␣ (HIF-1␣) subunit expression and transcriptional activity. Indeed, HIF-1␣ was reciprocally modulated by insulin and insulin-like growth factor pathways (1,32,69,72,80).…”
mentioning
confidence: 99%